The enforcement of mandatory disclosure rules - Matthias Dahm; Paula González; Nicolás Porteiro (The University of Nottingham, Centre for Decision Research and Experimental Economics (CeDEx), 2016)
This paper examines the incentives of a firm to invest in information about the quality of its product and to disclose its findings. If the firm holds back information, it might be detected and fined. We show that optimal monitoring is determined by a trade-off. Stricter enforcement reduces the incentives for selective reporting but crowds out information search. Our model implies that (i) the probability of detection and the fine might be complements; (ii) the optimal monitoring policy does not necessarily eliminate selective reporting entirely; (iii) even when there is some selective reporting in equilibrium and more stringent monitoring is costless, increasing the probability of detection might not be beneficial; and (iv) when society values selectively reported information, the optimal fine might not be the largest possible fine.
Keywords: D82; L15; 330; strategic information transmission; distrust effect; confidence effect; monitoring; penalty; fine; sanction; detection probability